Food rebalancing in a complex with relaxation exercises improves performance, body structure, metabolism during a lost of weight body in elite judokamen - Le Panse, B.; Sutter, T.; Popova, T. V.; Volkova, K.; Kourova, O. G. (Journal of Physical Education and Sport, 2020)
Objective Background Periodic weight loss is often necessary for judo athletes. The health of bones during weight loss in judokas has not been previously investigated. We assessed a new method of rebalancing diet, which is based on the circadian rhythm of various hormones. In addition, the psychophysiological functions of 12 male athletes (28 years old) were examined. The athletes engaged in judo training at a professional level and regularly (3_4 times a year) practiced fast weight reduction. Materials and Methods We assessed 12 elite judoist men. They followed the LE PANSE method for 10 months. This method is based on hormonal peaks as well as individualized personalized training and medical attention to the subject. Lean mass(LM), fat mass (FM), lumbarspine (LS), total hip (TH), and whole body (WB) were measured using DEXA. Electroencephalography and the Spielberg methods of self-evaluation of anxiety were used. Results The LE PANSE method significantly increases bone density at all sites studied (-2.7 % whole body; 8.7% total hip, and 3.7% lumbar spine (p<0.05), decreases fat mass (-37.7%) (p<0.05) and preserves muscle mass. Studies conducted after psychophysical correction showed a decrease in functional tension in athletes. Conclusions Our data suggest that the LE PANSE method decreases fat mass, preserves muscle mass, and increase BMD at all sites measured without alteration in performance during national and international championships. The correction of the psychophysical state of athletes practicing weight loss, using the method of balanced nutrition Le Pans, will help to maintain the optimal functional state of the body and improve athletic performance.